PARTISIPASI DAN PERAN PEREMPUAN DALAM PARTAI POLITIK - Rahim, Abdul (An - Nisa`, 2010)
Participation of woman in political parties is quite high in managerial, organizational meetings, voting, campaigns, political discussions and public meetings that have been carried out by many exsiting political parties. However, the main problem in womanâs political activities is the appearance of in justice as a result of the disparities between womanâs political rights and participation at one side and the political rights and roles of men on the other side. Recently the role of woman in political parties is just ordinary member of an organization. Several informants say that woman who are members of an organization mostly do not have much experience in organizing and do not possess courageous characteristics as men generally do. For this reason, many working programs proposed by woman are not accepted and implemented into the existing political world. The position of woman in political parties is generally is stereotype. The factors that affect womanâs involvement in political parties are: the influence of their educational background, which mainly determines the activeness of woman in their involvement as the member of political party, because all the tasks entrusted to woman can be implemented due to the education possessed by these woman. This means that there is a relevancy between their educational background and their duties.Some constraints experienced by woman in political parties are based on several issues including educational background, jobs, gender equality and justice, domestic role, patriarchal culture, religion, and family relationships.